Current guidelines for the management of adrenal incidentalomas in European countries - Ząber, Julia; Wyleciał, Zuzanna; Dąbrowski, Patryk; Guzik, Marcelina; Pyla, Eliza (Quality in Sport, 2025)
Introduction and purpose: Adrenal incidentalomas are increasingly detected due to the widespread use of advanced imaging techniques, presenting a growing clinical challenge. These adrenal masses, often discovered unintentionally, necessitate careful evaluation to differentiate between benign and malignant lesions, as well as hormonally active and inactive tumors. Despite a shared clinical concern, the management of adrenal incidentalomas varies across European countries, reflecting differences in healthcare systems, access to resources, and interpretation of evidence-based practices. This article aims to provide an overview of the current guidelines adopted by various European nations, highlighting areas of consensus and divergence, and exploring their implications for clinical practice and patient outcomes. Materials and methods: A literature search was conducted by analysing scientific articles published in Google Scholar, PubMed, and UpToDate using keywords included: incidentaloma, adrenal glands, hormonal activity, malignancy. We also searched current recommendations of The Endocrine Society Clinical Practice Guidelines. Description of the state of knowledge: Adrenal incidentalomas are asymptomatic adrenal masses detected incidentally during imaging studies performed for unrelated reasons. The clinical importance of these lesions lies in their potential for hormonal activity and malignancy. This article aims to evaluate the current strategies and guidelines for hormonal assessment in patients with adrenal incidentalomas. A systematic hormonal workup is essential to identify subclinical hormone secretion, particularly autonomous cortisol secretion, pheochromocytoma, and primary aldosteronism. Conclusion: Timely and accurate hormonal evaluation is crucial for risk stratification and guiding management decisions, including surveillance or surgical intervention. This assessment is key to preventing potential complications and improving patient outcomes.